Diabetes is associated with greater leg pain and worse patient-reported outcomes at 1 year after lumbar spine surgery - Kosei Nagata (Nature Portfolio, 2021)
Abstract Although patients with diabetes reportedly have more back pain and worse patient-reported outcomes than those without diabetes after lumbar spine surgery, the impact of diabetes on postoperative recovery in pain or numbness in other regions is not well characterized. In this study, the authors aimed to elucidate the impact of diabetes on postoperative recovery in pain/numbness in four areas (back, buttock, leg, and sole) after lumbar spine surgery. The authors retrospectively reviewed 993 patients (152 with diabetes and 841 without) who underwent decompression and/or fixation within three levels of the lumbar spine at eight hospitals during April 2017–June 2018. Preoperative Numerical Rating Scale (NRS) scores in all four areas, Oswestry Disability Index (ODI), and Euro quality of life 5-dimension (EQ-5D) were comparable between the groups. The diabetic group showed worse ODI/EQ-5D and greater NRS scores for leg pain 1 year after surgery than the non-diabetic group. Although other postoperative NRS scores tended to be higher in the diabetic group, the between-group differences were not significant. Diabetic neuropathy caused by microvascular changes may induce irreversible nerve damage especially in leg area. Providers can use this information when counseling patients with diabetes about the expected outcomes of spine surgery.